APPLICATION OF MODEL PREDICTIVE CONTROL (MPC) TUNING STRATEGY IN MULTIVARIABLE CONTROL OF DISTILLATION COLUMN - A. Ahmad; A. Wahid (Reaktor, 2007)
A model predictive control strategy is proposed for multivariable nonlinear control problem in a distillation column. The aim is to provide a solution to nonlinear control problem that is favorable in terms of industrial implementation. The scheme utilizes multiple linear models to cover wider range of operating conditions. Depending on the operating conditions, suitable model is used in control computations. Servo and regulatory controls of the system are examined. Comparisons are made to conventional controllers. The results confirmed the potentials of the proposed strategy.